Cancer incidence and cancer death in relation to tobacco smoking in a population‐based Australian cohort study. Issue 5 (31st May 2021) - Weber, Marianne F.; Sarich, Peter E. A.; Vaneckova, Pavla; Wade, Stephen; Egger, Sam; Ngo, Preston; Joshy, Grace; Goldsbury, David E.; Yap, Sarsha; Feletto, Eleonora; Vassallo, Amy; Laaksonen, Maarit A.; et al.
Abstract: Tobacco smoke is a known carcinogen, but the magnitude of smoking‐related cancer risk depends on country‐specific, generational smoking patterns. We quantified cancer risk in relation to smoking in a population‐based cohort, the 45 and Up Study (2006‐2009) in New South Wales, Australia. Cox proportional hazards regressions estimated adjusted hazard ratios (HR) by self‐reported smoking history at baseline (2006‐2009) for incident, primary cancers via linkage to cancer registry data to 2013 and cancer death data to 2015. Among 229 028 participants aged ≥45 years, 18 475 cancers and 5382 cancer deaths occurred. Current‐smokers had increased risks of all cancers combined (HR = 1.42, 95% confidence interval [CI], 1.34‐1.51), cancers of the lung (HR = 17.66, 95%CI, 14.65‐21.29), larynx (HR = 11.29, 95%CI, 5.49‐23.20), head‐and‐neck (HR = 2.53, 95%CI, 1.87‐3.41), oesophagus (HR = 3.84, 95%CI, 2.33‐6.35), liver (HR = 4.07, 95%CI, 2.55‐6.51), bladder (HR = 3.08, 95%CI, 2.00‐4.73), pancreas (HR = 2.68, 95%CI, 1.93‐3.71), colorectum (HR = 1.31, 95%CI, 1.09‐1.57) and unknown primary site (HR = 3.26, 95%CI, 2.19‐4.84) versus never‐smokers. Hazards increased with increasing smoking intensity; compared to never‐smokers, lung cancer HR = 9.22 (95%CI, 5.14‐16.55) for 1‐5 cigarettes/day and 38.61 (95%CI, 25.65‐58.13) for >35 cigarettes/day. Lung cancer risk was lower with quitting at any age but remained higher than never‐smokers for quitters aged >25y. By age 80y, an estimated 48.3% of current‐smokers (41.1% never‐smokers) will develop cancer, and 14% will develop lung cancer, including 7.7% currently smoking 1‐5 cigarettes/day and 26.4% for >35 cigarettes/day (1.0% never‐smokers). Cancer risk for Australian smokers is significant, even for 'light' smokers. These contemporary estimates underpin the need for continued investment in strategies to prevent smoking uptake and facilitate cessation, which remain key to reducing cancer morbidity and mortality worldwide.